KEARIFAN LOKAL DAN DINAMIKA EKONOMI DI KAWASAN SEJARAH AL-ZAYTUN DALAM PERSPEKTIF DAKWAH DAN PENDIDIKAN - Fitriyani; Istikhomah; cacih; Hasibuan, Madu Madonna Uli; Aulia, Friska; Suryandari, Meity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the role of local wisdom and economic dynamics in the historical area of Al-Zaytun from the perspective of da'wah (Islamic propagation) and education. This area not only holds historical value but also serves as a center for religious, social, and economic activities based on local values. The research method used is a qualitative study with a descriptive-analytical approach. The findings of the study indicate that: 1) Local Wisdom as a Socio-Cultural Foundation: The historical area of Al-Zaytun possesses strong elements of local wisdom, such as mutual cooperation (gotong royong), tolerance, and appreciation for spiritual and traditional values. These values shape the community into one that is ethical and religious in character. 2) The Role of Economy in Da'wah and Education: Economic activities flourishing around Al-Zaytun ranging from agriculture to micro, small, and medium enterprises (MSMEs), as well as services contribute significantly to local economic development. These activities also serve as a medium for da'wah bil hal (preaching through actions) and support the self-reliance of Islamic educational institutions. 3) Integration of Da'wah, Education, and Economy: Al-Zaytun is not only a center of religious education but also a hub for economic and social empowerment. This model demonstrates the synergy between da'wah, education, and a local wisdom-based economy, which can serve as a development model for other Islamic historical regions in Indonesia. 4) Dynamics and Challenges: Despite its development, the area faces challenges such as negative stereotypes, limited market access, and dependence on central figures. These issues call for stronger governance and a more inclusive approach. Keywords: Local Wisdom, Economic Dynamics, Al-Zaytun, Da'wah, Educatio.